2023
DOI: 10.3390/jmse11030596
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Performance of Passive Pre-Chamber on a Lean-Burn Natural Gas Engine under Low Load

Abstract: Stable ultra-lean combustion is an effective way for natural gas engines to reduce NOx emissions, but it also has higher requirements for ignition stability. The passive pre-chamber can effectively increase the ignition energy and extend the lean-burn limit of natural gas engines. However, the scavenging capacity of the pre-chamber limits its performance under low engine load. In this paper, several passive pre-chambers are designed, and the CFD simulation is carried out to investigate the influence of directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Nonetheless, it is essential to note that each In recent years, pre-chamber technology has gained interest as a means to facilitate the use of renewable fuels in ICEs, next to improving combustion with classic fossil fuels. Research has explored the feasibility of employing pre-chambers with a variety of renewable fuels [110,[117][118][119][120][121]. Many of these possess high octane numbers, rendering them challenging to ignite in CI engines.…”
Section: Pre-chambermentioning
confidence: 99%
“…Nonetheless, it is essential to note that each In recent years, pre-chamber technology has gained interest as a means to facilitate the use of renewable fuels in ICEs, next to improving combustion with classic fossil fuels. Research has explored the feasibility of employing pre-chambers with a variety of renewable fuels [110,[117][118][119][120][121]. Many of these possess high octane numbers, rendering them challenging to ignite in CI engines.…”
Section: Pre-chambermentioning
confidence: 99%
“…Lu et al [32] investigated the influence of nozzle hole design parameters of a prechamber on the scavenging process under low loads using CFD. They found that with increasing nozzle diameter from 0.8 to 1.6 mm, the residual gas discharge decreased to 1% from 5.9%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Properly designed pre-chambers can significantly extend engine lean-burn limit of the engine and increase efficiency [28], but one of the disadvantages of integrating a prechamber into an engine head is the associated cost. Installation of a pre-chamber requires modification of the cylinder head, which may necessitate a redesign of coolant passages or other features.…”
Section: Introductionmentioning
confidence: 99%